Perkembangan Kediri Stoomtram Maatschappij Pada Tahun 1895 - 1930 - Hafid, Hafid (Universitas Negeri Surabaya, 2023)
Kediri is one of the areas in East Java that has fertile soil. No wonder if since the 19th century the Dutch people aggressively built the agricultural and plantation industries to develop the center of agriculture and plantations that exist there. Entering the 20th century marked by the development of economic development development in Kediri, emerged tramway modes founded by Kediri Stoomtram Maatschappij (KSM) in 1895. KSM is a tram transportation services company that transports the goods and passengers from one place to another. The tram line of KSM runs from Jombang to Pare and ends in Kediri. For goods transport services, KSM transported plantation and agricultural products from industries in Kediri and Jombang. For services of passenger transport, KSM provides passenger train service of 1st, 2nd and 3rd class, which in the end in 1920 the 1st class service is removed and leaving only 2nd and 3rd class services. KSM has an influence on social and economic aspects. Social aspect is in the form of human mobility and goods. As for the economic aspect, KSM is able to create jobs for indigenous people. In this study using historical research methods. The objectives of this research are 1) To analyze the economic development and transportation facilities in Kediri area before the establishment of KSM, 2) To analyze the development of Kediri Stoomtram Maatschappij in 1895 -1930, and 3) To analyze the impact of Kediri Stoomtram Maatschappij development on regional development Kediri. Keywords: Tram, KSM, Economy